Experience of establishing and coordinating a nationwide network for bidirectional intussusception surveillance in India: lessons for multisite research studies - Rakesh Kumar; Ashish Wakhlu; Manoja Kumar Das; Narendra Kumar Arora; Atul Gupta; John Mathai; Bhadresh R Vyas; Pavai Arunachalam; Cenita J Sam; Arindam Ray; Javeed Iqbal Bhat; Jayanta K Goswami; et al. (BMJ Open)
Objectives To document and share the process of establishing the nationally representative multisite surveillance network for intussusception in India, coordination, data management and lessons learnt from the implementation.Design This study combined both retrospective and prospective surveillance approaches.Setting 19 tertiary care institutions were selected in India considering the geographic representation and public and private mixParticipants All children under-2 years of age with intussusceptionPrimary and secondary outcome measures The experience of site selection, regulatory approvals, data collection, quality assurance and network coordination were documented.Results The site selection process involved systematic and objective four steps including shortlisting of potential institutions, information seeking and telephonic interaction, site visits and site selection using objective criteria. Out of over 400 hospitals screened across India, 40 potential institutions were shortlisted and information was sought by questionnaire and interaction with investigators. Out of these, 25 institutes were visited and 19 sites were finally selected to participate in the study. The multistep selection process allowed filtering and identification of sites with adequate capacity and motivated investigators. The retrospective surveillance documented 1588 cases (range: 14–652 cases/site) and prospective surveillance recruited 621 cases (range: 5–191 cases/site). The multilayer quality assurance measures monitored and ensured protocol adherence, complete record retrieval and data completeness. The key challenges experienced included time taken for obtaining regulatory and ethical approvals, which delayed completion of the study. Ten sites continued with another multisite vaccine safety surveillance study.Conclusion The experience and results of this systematic and objective site selection method in India are promising. The systematic multistep site selection and data quality assurance methods presented here are feasible and practical. The lessons from the establishment and coordination of this surveillance network can be useful in planning, selecting the sites and conducting multisite and surveillance studies in India and developing countries.